Influence of structural instability at the creep characteristics of constructing materials - Karaseva, E.V. (Вопросы атомной науки и техники, 2015)
The structural instability, which observed during the creep of constructing materials in different structural states, is the result from changes in the geometry of the applied stresses and strain rate and significantly influences on the creep characteristics. It is shown that the result of appearance of structural instability and the subsequent restructuring of Zr, ZrlNb, and Nb, subjected to severe plastic deformation, was the change in the law creep. Transformation of the structure of the steel 15Cr2NMFA during creep leads to changes in the character of plastic flow, the appearance of jumplike creep deformation especially at stresses close to the ultimate strength. Нестабільність структурного стану, що спостерігається в умовах повзучості конструкційних матеріалів у різних структурних станах, є наслідком зміни геометрії прикладених напруг і швидкості деформування та істотно впливає на характеристики повзучості. Показано, що наслідком виникнення структурної нестабільності і подальшої перебудови структури для Zr, ZrlNb і Nb, що піддавалися інтенсивним пластичним деформаціям, є зміна закону повзучості. Перебудова структури в процесі повзучості сталі 15Х2НМФА призводить до зміни характеру пластичної течії і появі стрибкоподібної деформації повзучості. Неустойчивость структурного состояния, наблюдаемая в условиях ползучести конструкционных материалов в различных структурных состояниях, является следствием изменения геометрии приложенных напряжений и скорости деформирования и существенно влияет на характеристики ползучести. Показано, что следствием возникновения структурной неустойчивости и последующей перестройки структуры для Zr, ZrlNb и Nb, подвергнутых большим пластическим деформациям, является изменение закона ползучести. Перестройка структуры в процессе ползучести стали 15Х2НМФА приводит к изменению характера пластического течения и появлению скачкообразной деформации ползучести.